EFFECTIVENESS AND EFFICIENCY IN A HURRIED WORLD: ONLINE CUSTOMERS KNOW WHAT THEY WANT - Laila Refiana Said; Noraina Noraina (BISMA: Jurnal Bisnis dan Manajemen, 2022)
Despite many studies on online purchasing decisions, e-marketing mix elements tend to be based solely on literature, regardless of what antecedents are appropriate for the target sample of research. Selecting research variables by salient factors determination method leads to several hypotheses about e-marketing mix elements that influence purchase decisions in one of the largest marketplaces in Indonesia, i.e., Shopee.co.id. The current study is expected to answer which elements in the e-marketing mix most determine purchase decisions in the digital era that demand the effectiveness and efficiency of resources. The total respondents were 150 university students. Structural Equation Modeling was utilized to analyze the data. Results showed that e-marketing mix elements that significantly influence purchasing decisions were e-process and e-price. The findings show that the most important online shopping factors were processing speed (time effectiveness) and lower product prices (cost efficiency). E-promotion did not significantly affect the purchase decision since online shopping has become a daily routine activity, especially since the Covid-19 pandemic in early 2020. Keywords: effectiveness, efficiency, e-marketing mix, marketplace, purchase decision